2022
DOI: 10.1111/mmi.14979
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in new flagellum tip attachment in bloodstream form African trypanosomes

Abstract: African trypanosomiasis is a vector-borne neglected tropical disease caused by parasites of the Trypanosoma genus that are cyclically transmitted through the bite of an infected tsetse fly. Two forms of the disease are endemic to sub-Saharan Africa: Human African Trypanosomiasis, also known as sleeping sickness, and Animal African Trypanosomiasis, commonly known as nagana (Aksoy et al., 2014). Nagana, caused by Trypanosoma brucei, Trypanosoma vivax, and Trypanosoma congolense, is considered to be the main dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…This suggested that TbSmee1 might be present at the “groove”. The groove is a structure involved in remodelling of the microtubule cytoskeleton during cell replication in bloodstream form T. brucei (Hughes et al, 2013; Smithson et al, 2022). It can be detected using the monoclonal antibody DOT1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggested that TbSmee1 might be present at the “groove”. The groove is a structure involved in remodelling of the microtubule cytoskeleton during cell replication in bloodstream form T. brucei (Hughes et al, 2013; Smithson et al, 2022). It can be detected using the monoclonal antibody DOT1.…”
Section: Resultsmentioning
confidence: 99%
“…At the time of the preprint of this work being published, TbSmee1 was the first protein besides the DOT1 antigen and FLAM3 to be shown to localise to the groove structure associated with the tip of the growing new FAZ (Sunter et al, 2015a). A number of additional proteins present at the groove have since been identified (Smithson et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Normalised fold-change in usage of annotation terms revealed a strongly disproportionately high usage of terms associated with the surface membrane and the endo/exocytic system (pellicular and flagellar membrane, ER and endocytic). There were also weaker biases in BSFs for 1) general (nucleus, nuclear lumen) rather than specific (nucleoplasm, nucleolus) nuclear localisation annotations, 2) fewer mitochondrion and kinetoplast annotations, 3) more glycosome terms, and 4) more flagellum tip and flagellar connector-like 5 , 35 annotation terms ( Figure 5A,B ). The BSF cell surface therefore has the greatest adaptation between BSFs and PCFs, with this change plausibly supported and/or maintained by changes in the ER and endocytic system.…”
Section: Resultsmentioning
confidence: 99%
“…Normalised fold-change in usage of annotation terms revealed a strongly disproportionately high usage of terms associated with the surface membrane and the endo/exocytic system (pellicular and flagellar membrane, ER and endocytic). There were also weaker biases in BSFs for 1) general (nucleus, nuclear lumen) rather than specific (nucleoplasm, nucleolus) nuclear localisation annotations, 2) fewer mitochondrion and kinetoplast annotations, 3) more glycosome terms, and 4) more flagellum tip and flagellar connector-like [5,25] annotation terms (Figure 4A,B). The BSF cell surface therefore has the greatest adaptation between BSFs and PCFs, with this change plausibly supported and/or maintained by changes in the ER and endocytic system.…”
Section: Resultsmentioning
confidence: 99%